ANALISIS KINERJA KARYAWAN BERBASIS PENGUKURAN DISIPLIN KERJA DAN KEPUASAN KERJA - Tara Ananda Permatasari; Rani Anwar (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2023)
This study aims to see the effect of work discipline and job satisfaction on the performance of employees of PT. Minanga Ogan (PKS SEII ENAI MILL). The data collection technique in this study was by distributing questionnaires. The results showed that the work discipline variable has a significant effect on employee performance partially. The relationship between work discipline and employee performance is an effort to carry out work activities properly. Furthermore, the partial or t test shows that there is an effect of job satisfaction on employee performance. The relationship between job satisfaction and performance must be well executed. The better the job satisfaction, the better the employee performance. Simultaneously the two variables, namely work discipline and job satisfaction affect employee performance. Employee performance is greatly influenced by work discipline and job satisfaction so that employees have high productivity which will have an impact on improving employee performance so that company goals will be achieved.